Teachers’ discourse practices in multilingual mathematics classrooms in nigerian secondary schools - Michael, Alexander (My University, 2019)
This study focused specifically on the Discourse practices of Mathematics teachers in multilingual classrooms of secondary schools in Nigeria. The Secondary School Mathematics classrooms were observed using the lens of Gee’s Discourse analysis theory and method and were to enable me to closely examine and understand the challenges of teachers in multilingual classrooms. The Discourse practice main categories (language and non-language practices) enabled me to identify and understand what mathematical Discourse practices existed in the multilingual classrooms. The main research question was: What Discourse practices were used by teachers as plainly evinced in their language (verbal and non-verbal) in northern Nigeria multilingual Mathematics classrooms? To answer this research question, I used these sub-questions i. How do teachers use language (verbal and non-verbal) to enact practices as reflected in their Discourses in the teaching and learning of Mathematics in multilingual classrooms in northern Nigeria? ii. Why do teachers use language (verbal and non-verbal) in their Discourse practices in multilingual Mathematics classrooms of northern Nigeria? The study adopted a qualitative research design. As is the case with most qualitative methods, the sample in this study was small and purposive. The sample consisted of four purposively selected multilingual Mathematics teachers in two Secondary Schools. Data gathering techniques for this study included video observations, written field notes and face-to-face reflective interviews in the Schools and classrooms. The language of description in this study refers to all the categories and sub-categories developed before, during and after my pilot of this study. These categories and sub-categories were developed from Gee’s Discourse analysis theory, reviewed relevant literature and the data gathered from the multilingual classrooms of Mathematics teachers. The empirical results of the analysis as presented in Chapters Six to Eight centered on the dominant Discourse practices such as mathematical explaining, mathematical reiterating, mathematical questioning, mathematical symbolising, mathematical re-voicing, mathematical gesturing and mathematical proceduralising. The empirical results of this study also showed that there was a projection of the high status of the identity of the Mathematics teachers. I also observed that Mathematics teacher allowed students to code-switch in their classroom interaction to help them verbalise their thinking as the majority of them were not proficient in the LoLT. The observations in the Mathematics classroom also suggested that teachers used the whole-class participation norm in form of teacher-led discussions and choral responses. In the light of the emergent issues in this study I, therefore, recommend workshops and in-service training for Mathematics teachers. This kind of training will enrich the teachers’ knowledge, help them to make enlightened decisions and use contextually appropriate methods of teaching students in multilingual classrooms.
A thesis submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand in fulfillment of the requirement for the degree of Doctor of Philosophy Johannesburg 2019